Conselhos de saúde: informação, poder e política social - Lima, Clóvis Ricardo Montenegro de (1993)
This dissertation describes certain health policy events, from 1986 to 1992, dealing with community participation and social control on the united Health System (sistema único de Saüde) :and also dealing with the organizatlon of the Múnicipal' Heal.t.h Council (Conselho Municipal de Saúde) of t.he city of Jbínville - state of santa Catarina, Brazil. This dissertation also discusses the concepts of information, power and social pOllcy, as well as the -possíbíLity of actíon by Health Councils, promoting changes in'the meaning of 'thehealth ccncept; .